2023
DOI: 10.3390/diagnostics13071211
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Precancerous Lesions of Hepatocellular Carcinoma: Recent Progress in Diagnosis

Abstract: The most common cause of hepatocellular carcinoma (HCC) is chronic hepatitis and cirrhosis. It is proposed that precancerous lesions of HCC include all stages of the disease, from dysplastic foci (DF), and dysplastic nodule (DN), to early HCC (eHCC) and progressed HCC (pHCC), which is a complex multi-step process. Accurately identifying precancerous hepatocellular lesions can significantly impact the early detection and treatment of HCC. The changes in high-grade dysplastic nodules (HGDN) were similar to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Combined with previous studies, it has been shown that enhanced scanning based on the characteristics of angiogenesis and blood supply changes in HCC tumors has a high diagnostic value for HCC ( 23 ). With an increasing level of malignancy, the blood supply to the portal vein and hepatic artery decreases, whereas that to the abnormal artery gradually increases ( 24 , 25 ). The combined application of AP hyperenhancement and washout can improve the diagnostic specificity of HCC ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with previous studies, it has been shown that enhanced scanning based on the characteristics of angiogenesis and blood supply changes in HCC tumors has a high diagnostic value for HCC ( 23 ). With an increasing level of malignancy, the blood supply to the portal vein and hepatic artery decreases, whereas that to the abnormal artery gradually increases ( 24 , 25 ). The combined application of AP hyperenhancement and washout can improve the diagnostic specificity of HCC ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“… High mobility group-Box 3 during hepatocellular carcinoma progression[ 21 , 31 - 33 , 35 ]. Based on the data of basic or clinical studies, the progressive upregulation of high mobility group-Box 3 (HMGB3) at the mRNA or protein level occurred from the normal liver to chronic hepatitis to liver cirrhosis to hepatocellular carcinoma (HCC).…”
Section: Hmgb-3 Signallingmentioning
confidence: 99%
“…The common etiological causes of liver cancer progression are persistent CH and LC. It has been suggested that precancerous lesions of the liver include all stages of the disease, from dysplastic lesions and dysplastic nodules to early liver cancer[ 33 , 34 ]. A dynamic model of hepatocyte malignant transformation was developed in male SD rats according to the China National Invention Patent (ZL201810077848.2) by using 2-fluorenylacetamide (2-FAA) as a carcinogen.…”
Section: Hmgb-3 Signallingmentioning
confidence: 99%
“…With a mortality-to-morbidity ratio of 0.95 (Chen et al, 2020), liver cancer is the most dangerous form of liver illness, and hepatocellular carcinomas (HCCs) are the most diagnosed malignancies of liver origin. The "trilogy pattern" describes how HCC develops and is characterized by cirrhosis, hepatitis B, and liver cancer (Liao et al, 2023). HCC is difficult to diagnose because symptoms do not occur until advanced stage or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%